Fluktuasi Total Padatan Tersuspensi (Total Suspended Solid) dan Kekeruhan di Selat Lombok - Boiris Benet Sinaga; Yulianto Suteja; I Gusti Bagus Sila Dharma (Fakultas Kelautan dan Perikanan Universitas Udayana, 2020)
Total suspended solid is particles or living components (biotics) such as phytoplankton, zooplankton, bacteria, fungi, or dead components (abiotics) such as detritus and solids (sand, mud, and clay) suspended in water.. Total suspended solids are related to turbidity. Therefore, turbidity and total suspended matter can be used as water quality parameters that can determine whether the water conditions are good or not. The Lombok Strait is semi-closed waters that are influenced by local influences such as input from the river. This will certainly affect the total suspended solids found in the Lombok Strait waters. This research was conducted in November 2017. Field sampling was carried out in the Lombok Strait waters at the point of 116 ° 1'18